The Competitiveness and Sustainability of Micro, Small, and Medium Enterprises in West Nusa Tenggara Province, Indonesia (Revisited) - Lalu Hamdani Husnan (International Journal of Small and Medium Enterprises and Business Sustainability, 2016)
This paper is based on a study which aimed to examine the capabilities of micro, small and medium enterprises (MSMEs) and how they can play more important role in the Province of West Nusa Tenggara. To fulfill this aim, a review of applicable theories was conducted. Also some interviews were carried out with a number of managers/owners of MSMEs related to their capabilities and government programs and policies in the Province. This study found that competitiveness and sustainability of MSMEs in the West Nusa Tenggara Province depend strongly on their, especially economic, technological, organizational, and management and leadership capabilities. The strategy that has to be developed and undertaken by local government together with industry, and further research in this area are also discussed in this paper